(untitled) (Research Journal, 2025)
This study investigates the relationship between financial system and the economic growth in the context of Nepal and also studies the relative merits of banking sector vs. capital market in promoting economic growth in Nepal. The empirical results using Johansen’s cointegrating vector error correction based on the model developed on the basis of Cobb-Douglas production function by using aggregate annual data from 1993/94 to 2022/23 suggests that the financial structure seems insignificant in explaining Nepal’s economic growth and the empirical results suggest that banking sector has relative merits over capital market in promoting economic growth over the long-run in Nepal. The gross fixed capital formation has significant and positive association in explaining the real GDP in the short-run. The results of Granger causality explain the uni-directional causality running from banking sector development to real GDP and the development of capital markets to real GDP. The result is consistent with the earlier findings in some developing economies and it has two important implications. First, the policy should focus on banking sector development by enhancing its quality and outreach as it better promotes economic growth in long run and second, the scope of capital market should be further expanded to real economic activities to channelize its impact on growth.